Osteogenic capability of autologous rabbit adipose-derived stromal cells in repairing calvarial defects - CHENG Shao-wen; LIN Zhong-qin; WANG Wei; ZHANG Wei; KOU Dong-quan; YING Xiao-zhou; CHEN Qing-yu; SHEN Yue; CHENG Xiao-jie; PENG Lei; LV Chuan-zhu (Chinese Journal of Traumatology, 2012)
【Abstract】Objective: To evaluate the in vitro and in vivo osteogenic capability of adipose-derived stromal cells (ASCs). Methods: ASCs were isolated from New Zealand white rabbits and determined by alkaline phosphatase (ALP) staining, von Kossa staining and alizarin red staining. Some specific markers of osteogenic differentiation, including ALP, osteocalcin (OCN), osteopontin (OPN) were examined by reverse transcription-polymerase chain reaction (RT-PCR). In vivo, demineralized bone matrix (DBM)-ASCs composites were implanted into the rabbit calvarial defects created at each side of the longitudinal midline. After 6 weeks, histologic properties of the transplants were analyzed. Results: ASCs were successfully induced into osteogenesis. ALP staining, von Kossa staining and alizarin red staining showed positive results. The expressions of ALP, OCN and OPN were detected in ASCs after cultivation in osteogenic medium. Extensive new bone was observed in the defects transplanted with DBM-ASCs composites. Conclusion: ASCs have the potential to differentiate into osteogenic lineage and DBM-ASCs constructs are a promising method for regeneration in bone defects. Key words: Adipose tissue; Bone regeneration; Osteogenesis